Introduction to imaging spectrometers - Wolfe, William L. (Tutorial texts in optical engineering, 1997)
The increased interest in imaging spectroscopy has arisen largely for technical reasons. This Tutorial Text first reviews the required background in optics, radiometry, imaging, spectral sensing and focal plane arrays. Then the principles of these subjects are applied to several specific problems to illustrate the way in which such instruments can be designed.